Implementasi Peraturan Perpajakan Dalam Reimbursement PPN Dalam Kondisi Pandemi Covid-19: Studi Kasus Pada Kangean Energy Indonesia Ltd. - Rini Syarif; Firni Oktaviani; Rizal Riyadi (Jurnal Aplikasi Bisnis Kesatuan, 2025)
Value Added Tax (VAT) is a form of tax levied in Indonesia and levied from every transaction of trade, sale, and purchase of goods and there are local services available for personal remuneration, corporate payers, and administrations. Declaration of Value Added Tax (VAT) is made using the Regular Notification Letter (SPT-Time VAT) instead of the Annual Value Increase Retirement Submission due to its accumulative nature by depositing to the bank using the SSP (Surat Setoran Pajak). Indonesian contractors are exempt from indirect taxes including land and building taxes (UN), value added tax (VAT), sales taxes, import tariffs, remuneration, and regional charges other than direct taxes such as income tax (PPh) and interest tax on profits and royalty (PBDR). Kangean Energy Indonesia Ltd. is required to submit a letter of request for reimbursement of PPN in the form of a softcopy of documents for SSP transactions in which the SSP recognized only the first submission and for Non SSP should be coordinated with the verifier in advance which then the request for VAT reimburse is submitted to SKK Migas for the amount of VAT placed in a particular bank/post to the state cash.Through one letter containing a statement of the CCS (Contract Contractor Cooperation) in which such submission can only be made at most 2 (two) weeks once in a month and supported by the documents required at the time of submission.In the system of demand refund (reimbursement) VAT in the condition of Covid-19 pandemic in Kangean Energy Indonesia Ltd. is regulated in accordance with the Regulation of the Minister of Finance No.119/PMK.02/2019.   Keywords: value added tax, reimbursement.